We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website.
Please click on "Accept cookies" if you agree to the setting of cookies. Cookies that do not require consent remain unaffected by this, see
cookie policy and privacy policy.
DECLINE COOKIES

#1**+4 **

I'm going to assume that there is an original equation of y=(-1/2)x+b with a y-value of 2 and an x-value of -3, solve for b.

\(2=-\frac{1}{2}(-3)+b\)

Multiply.

\(2=\frac{3}{2}+b\)

Subtract b from both sides.

\(\frac{4}{2}-\frac{3}{2}=b\)

\(b=\frac{1}{2}\)

Now plug back into original equation.

\(y=-\frac{1}{2}x+\frac{1}{2}\)

In a problem with mx+b format, m is the slope, or in this problem \(m=-\frac{1}{2}\).

AdamTaurus Nov 15, 2017